Decoding atypical laryngeal growths – A case report - Dutta, Meghna; Ghosh, Abhik; Chatterjee, Suddhasatwya; Khan, Enam Murshed (Eastern Journal of Medical Sciences, 2022)
Respiratory  papillomatosis  is  a  relatively  rare  disease  with  a  potential  for  devastating  consequences.  The  viral  etiology  of  this  condition  has  been  well  established.  Most  often,  the  wart  is  successfully  managed  surgically.  Post  surgical  removal,  there  exists  a  high  chance  of  recurrence  of  the  papilloma.  It  has  been  documented  that  surgical  removal  followed  by  an  adjuvant  therapy  helps  to  delay  the  recurrence.  Also,  the  use  of  quadrivalent  human  papillomavirus  vaccine  is  expected  to  decrease  the  incidence  of  respiratory  papillomatosis  or  help  with  treatment  of  the  disease  in  the  years  to  come.  Here  we  discuss  an  unusually  late  presentation  of  adult-onset  laryngeal  papilloma  that  was  managed  with  some  deviation  from  the  routine.